Phytochemical analysis of Elateriospermum tapos and its inhibitory effects on alpha-amylase, alpha-glucosidase and pancreatic lipase - Ja'afar, Nor Liyana; K Thiagarajan, Siroshini; MB, Nurul Syahirah; Chang, Wei Lin; Shafie, Nurul Husna; Arapoc, Daryl Jesus; Abdul Kadir, Khairul Kamilah; Bahari, Hasnah (Forest Research Institute Malaysia, 2018)
Elateriospermum tapos contains high unsaturated fat and phytochemicals with many health benefits. This paper focuses on activities and inhibitory effects of E. tapos on digestive enzymes. Cold water, hot water and 70% ethanol extracts of the seed and shell of the fruit of E. tapos were used in this study. The extracts were screened for antioxidant activity, total phenolic content, total flavonoid content, and inhibitory effects on α-amylase, α-glucosidase and pancreatic lipase. Hot water extraction of shell of the E. tapos fruit had the highest total phenolic content (1298.60 ± 4. 24 µg GAE 100 g-1), total flavonoid content (16685.58 ± 487.77 µg CE 100 g-1) and antioxidant activity by 2, 2-diphenyl-2-picrylhydrazyl and β-carotene methods (84.16 and 122.17% respectively). The seed cold extract showed maximum α-amylase inhibition with IC50 (half maximal inhibitory concentration) of 0.03 mg mL-1. The lowest IC50 (0.02 mg mL-1) for α-glucosidase inhibition was from seed ethanol extracts while shell cold extract had the lowest IC50 for pancreatic lipase inhibition (37.80 mg mL-1). Results confirmed E. tapos as potential antioxidant and inhibitor of digestive enzymes for lipid (pancreatic lipase) and carbohydrate (α-amylase and α-glucosidase) which are beneficial to combat obesity and diabetes.